Transcriptional Adaptation of Mycosphaerella graminicola to Programmed Cell Death (PCD)of Its Susceptible Wheat Host - Keon, J.; Antoniw, J.; Carzaniga, R.; Deller, S.; Ward, J.L.; Baker, J.M.; Beale, M.H.; Beale, M.H.; Rudd, J.J.
Many important fungal pathogens of plants spend long periods (days to weeks)of their infection cycle in symptomless association with living host tissue, followed by a sudden transition to necrotrophic feeding as host tissue death occurs. Little is known about either the host responses associated with this sudden transition or the specific adaptations made by the pathogen to invoke or tolerate it. We are studying a major host-specific fungal pathogen of cultivated wheat, Septoria tritici (teleomorph Mycosphaerella graminicola). Here, we describe the host responses of wheat leaves infected with M. graminicola during the development of disease symptoms and use microarray transcription profiling to identify adaptive responses of the fungus to its changing environment. We show that symptom development on a susceptible host genotype has features reminiscent of the hypersensitive response, a rapid and strictly localized form of host programmed cell death (PCD)more commonly associated with disease-resistance mechanisms. The initiation and advancement of this host response is associated with a loss of cell-membrane integrity and dramatic increases in apoplastic metabolites and the rate of fungal growth. Microarray analysis of the fungal genes differentially expressed before and after the onset of host PCD supports a transition to more rapid growth. Specific physiological adaptation of the fungus is also revealed with respect to membrane transport, chemical and oxidative stress mechanisms, and metabolism. Our data support the hypothesis that host plant PCD plays an important role in susceptibility towards fungal pathogens with necrotrophic lifestyles.
Keywords: CYTOCHROME C RELEASE; DNA FRAGMENTATION; 1H-NMR; MYCOSPHAERELLA FIJIENSIS; PYCNIDIA; REACTIVE OXYGEN SPECIES